Food intake in relation to obesity and subjective cognitive complaints : a cross-sectional study from Nigeria - Ogundele, Olusegun Emmanuel; Awofala, Adeyemi Abayomi; Awofodu, Adebola Daniel; Ojo, Folasade Tinuade (Penerbit Universiti Kebangsaan Malaysia, 2022)
There is evidence from research that dietary lifestyle influences health and mental well-being but there is limited understanding of the mechanism in Nigerian adult population. This study evaluated association of food intake with obesity and subjective cognitive complaints (SCCs) in Nigerian adults. We carried out a cross-sectional study of 1338 random samples aged 18-87 years who were visiting six different public hospitals in the southwest Nigeria between March 2016 and April 2016. Standard food frequency questionnaire (FFQ) and SCC questionnaire were used while anthropometric data were measured using standard clinical procedures. Associations were determined by linear and unconditional logistic regressions, after adjustment for age, ethnicity, education, gender, marital status, family type, alcohol and smoking status. Consumption of four different foods was significantly associated with SCC while one food intake was significantly associated with obesity measure (i.e., body mass index): meat product (Adjusted Odds Ratio (AOR), 1.002; 95% Confidence Interval (CI), 1.001-1.004; P <.0001), and sugary snacks (AOR, 1.007; 95% CI, 1.002- 1.011; P <.01) were associated with increased SCCs whereas consumption of cereal products (AOR, 0.999; 95% CI, 0.998-1.000; P <.01) and potatoes (AOR, 0.998; 95% CI, 0.996-1.000; P <.05) were associated with decreased levels of SCCs. Consumption of non-alcoholic beverages was associated with decreased BMI levels (AOR, 0.998; 95%CI, 0.997-1.00; P <.05). Linear regression analyses on these data largely recapitulated the results. In conclusion, consumption of cereals, potatoes and non-alcoholic beverages appear beneficial to health and the findings could serve as an intervention strategy for tackling SCCs and obesity.